A co-creation of learning and teaching typology: What kind of co-creation are you planning or doing? - Bovill, Catherine (International Journal for Students as Partners, 2019)
In higher education discourse, reference to co-creation, partnership, and student engagement (to name but a few of the commonly used terms), covers a very wide range of different research and practice. This variety can often be confusing. In response, I present a co-creation oflearning and teaching typology, which is a practical resource intended to support students and staff to reflect on, and discuss, their planned and current practice and to be able to identify what particular kind of co-creation they are planning or doing. The typology can be used individually, in small groups or at an institutional level. It has been designed to be adaptable and includes space for additional co-creation variables and responses to be added. Informal feedback from using the typology suggests it has the potential to be (a) a planning tool, (b) a reflective tool, and (c) a mapping tool.